Psychiatric Symptoms in Acute Intermittent Porphyria - Case Report and Course of Treatment Using Placebo - Kosiba, Waldemar; Prystacka-Szar, Dominika; Siemko, Jakub; Kupczak, Wojciech (Journal of Education, Health and Sport, 2025)
Introduction: Acute intermittent porphyria is a disease inherited in an autosomal dominant manner, occurring with a frequency of 1:75,000 people. The main symptom of the disease is paroxysmal, colicky abdominal pain, which is accompanied by neuropsychiatric symptoms. For some patients, psychiatric symptoms are the only symptom of the disease. In this paper, the case of a 43-year-old patient struggling with recurrent colicky abdominal pain and depressive and anxiety disorders, which intensify during exacerbation periods, is presented, featuring an ambiguous diagnosis of porphyria in previous laboratory tests. In the treatment, glucose infusions, morphine, psychiatric and psychological therapy were used - saline solution was administered as a placebo. Aim: The aim of this paper is to highlight the difficulties in diagnosing psychiatric symptoms during an acute attack of porphyria, which significantly complicate its treatment, and to consider the possibility of using placebo as one of the elements in the diagnostic and therapeutic plan in order to optimize treatment and avoid complications by using smaller doses of narcotic drugs. Review methods: A thorough analysis of research studies available on PUBMED was conducted using the following keywords: acute intermittent porphyria; porphobilinogen; depression; anxiety disorders; psychiatry; placebo. The medical history of a 43-year-old female patient, suspected of having acute intermittent porphyria due to recurrent abdominal pain and psychiatric symptoms, was also analyzed. Conclusion: Our case illustrates how psychiatric symptoms can complicate the diagnosis of acute intermittent porphyria. Failing to recognize acute porphyria also carries the risk of life-threatening complications and may lead to unnecessary pharmacotherapy and stigmatization as a mental illness. This case demonstrates that placebo can be one of the components of a diagnostic and therapeutic plan of acute intermittent porphyria.